Memahami Peran Penting Museum Palagan Perjuangan 1945 Bojongkokosan Sebagai Pengingat Sejarah Pertempuran Bojongkokosan - Fhauziah Sri Ayuning Putri; Hikmaludin Abror; Gabriel Sandrinamora Wilhem Simamora; Yogi Muhamad Dava (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This research aims to; (1) Describing the history of the Battle of Bojongkokosan, (2) Knowing the function of the Bojongkokosan Palagan Perjuangan 1945 Museum, (3) Collections and dioramas at the Bojongkokosan Palagan Perjuangan 1945 Museum, (4) Knowing the role of the local community in preserving the Bojongkokosan Palagan Perjuangan 1945 Museum as a form of historical reminder. This research uses qualitative data analysis methods and library research methods, by obtaining information by utilizing existing facilities in libraries and online sources such as books, documents, journals, or pure library research related to the research object. The results of the research and discussion show that, (1) The history of the Bojongkokosan battle, (2) This museum functions as an appropriate means of preserving historical heritage objects, as a means of education, a means of recreation, and a means of cultural attractions for the community., (3) The collections and dioramas at the Bojongkokosan Palagan Perjuangan 1945 Museum include reliefs, traditional weapons, war helmets, Molotov cocktails, replicas of Wago panzer tanks, knives, firearms, and the names of the fighters. (4) The role of the local community in preserving the Bojongkokosan Palagan Perjuangan 1945 Museum as a form of historical reminder. It is hoped that this article will broaden readers' insight so that they become more familiar with the Bojongkokosan Palagan Perjuangan 1945 Museum which tells the story of the Bojongkokosan battle which is often forgotten.